Dam-Induced Hydrologic Alterations in the Rivers Feeding the Pantanal - Ely, Pedro; Fantin-Cruz, Ibraim; Tritico, Hans M.; Girard, Pierre; Kaplan, David (Frontiers in Environmental Science, 2020)
Tropical river basins have experienced dramatically increased hydropower development over the last twenty years. These alterations have the potential to cause changes in hydrologic and ecologic systems. One heavily impacted system is the Upper Paraguay River Basin, which feeds the Pantanal wetland. The Pantanal is a Ramsar Heritage site and is one of the world’s largest freshwater wetlands. Over the past twenty years, the number of hydropower facilities in the Upper Paraguay River Basin has more than doubled. This paper uses the Indicators of Hydrologic Alteration (IHA) method to assess the impact of twenty-four of these dams on the hydrologic regime over twenty years (10 years before and 10 years after dam installation) and proposes a method to disentangle the effects of dams from other drivers of hydrologic change using undammed “control” rivers. While most of these dams are small, run-of-the-river systems, each dam significantly altered at least one of the 33 hydrologic indicators assessed. Across all studied dams, 88 of the 256 calculated indicators changed significantly, causing changes of 5 to 40%, compared to undammed reaches. These changes were most common in indicators that quantify the frequency and duration of high and low pulses, along with those for the rate and frequency of hydrologic changes. Importantly, the flow regime in several undammed reaches also showed significant alterations, likely due to climate and land-use changes, supporting the need for measurements in representative control systems when attributing causes to observed change. Basin-wide hydrologic changes (in both dammed and undammed rivers) have the potential to fundamentally alter the hydrology, sediment patterns, and ecosystem of the Pantanal wetland. The proposed refinement of the IHA methods reveals crucial differences between dam induces alteration and those assigned to other drivers of change; these need to be better understood for more efficient management of current hydropower plants or the implementation of future dams.